A terminology affair in pregnants and neonates: herpes gestationis or pemphigoid gestationis? - Shelleh, H.H.; Dawood, S. (European Journal of Pediatric Dermatology, 2006)
Herpes gestationis is a bullous gestational disease which affects the pregnant mothers and rarely their newborns. The term "herpes gestationis" is an outdated one, and not justified in the light of recent etiological facts. It is an immunological reaction to paternal antigens, not related at all to any of the human herpes viruses and has certainly no relation with herpetic diseases as the terminology (herpes gestationis) indicates. This term is not only wrong on etiology wise, but may also create a lot of confusion to the patient and family by its vulgar herpetic term, which every patient fears. We think that the term "pemphigoid gestationis" should have the priority over the old term herpes gestationis in our medical practice and medical publications as it represents more closely the facts about this bullous gestational disease, and cleans the historical herpetic "contamination" of the terminology.